A Complex of Risk Factors for Developing Dependence on the Combined Abuse of Hashish and Tramadol - Inara Khayredinova1, Zarifjon Ashurov2, Indira Giyazitdinova3, Mark Agranovsky4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: The study of a set of risk factors for a social-premorbid narcological personality dependenton the combined abuse of hash and tramadol.Materials and Method: 129 male patients were examined, which were divided into three groups. Group I(main) -41% of patients (n = 53) with a combined abuse of hashish and tramadol, Group II (1 control) -34%of patients (n = 44) with addiction from opiates abusing tramadol without a doctor’s prescription, groupIII (2 control) - 24.8% of patients (n = 32) with a cannabis addiction F12.2. The influence of biological,socio-psychological and personality risk factors on the development of the formation of premorbid-socialnarcological personality was analyzed. To identify the strength of the relationship between exposure to thefactor and the disease, the relative risk (RR) was calculated.Results: An analysis showed a combination of factors of involvement in psychoactive substances: thepresence of a family history of hereditary alcoholism and drug addiction in relatives of -62.3% (P <0.001 andP <0.001), transferred craniocerebral loss of consciousness injuries-39.6% (P <0.05), inferior family-73.6%(P <0.01; P <0.01), single child-50.9% (P <0, 05; P <0.05) or senior - 41.5% (P <0.05), unstable personalitytype - 50.9% (p <0.05, p <0.001).Conclusion: The analysis of premorbid-social indicators revealed a relative risk of the formation of anarcological personality and thereby determined a new set of factors for which an algorithm of primaryprevention measures was developed.